2017
DOI: 10.1111/jgh.13750
|View full text |Cite
|
Sign up to set email alerts
|

Dementia, cognitive impairment and proton pump inhibitor therapy: A systematic review

Abstract: Based on the current published literature, this systematic review has identified that the reported association between PPI use and dementia is limited by methodological issues and conflicting results. Further longitudinal studies with robust bias limitation are required to explore the use of PPIs and dementia or acute cognitive impairment, and to ascertain the existence of any causal relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 52 publications
1
46
0
2
Order By: Relevance
“…An alternative mechanism for the observed association between PPI use and cardiovascular risk is esomeprazole accelerating endothelial senescence, via inhibition of proteostasis and accumulation of protein aggregates linked to endothelial dysfunction . This mechanism would also explain an association between PPI use and risk of chronic kidney disease and vascular dementia …”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism for the observed association between PPI use and cardiovascular risk is esomeprazole accelerating endothelial senescence, via inhibition of proteostasis and accumulation of protein aggregates linked to endothelial dysfunction . This mechanism would also explain an association between PPI use and risk of chronic kidney disease and vascular dementia …”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis conducted by Wijarnpreecha, Thongprayoon, Panjawatanan, and Ungprasert () failed to find a significant association between PPI use and an increased risk of dementia with a between‐study heterogeneity of 99%. In conclusion, the evidence supporting an association between an increased risk of dementia and PPI use is actually quite limited (Batchelor et al, ) and might have been initially overestimated. These data are reassuring because PPIs are among the most widely used drug classes.…”
Section: Resultsmentioning
confidence: 93%
“…Although most epidemiological studies suggest that PPI use does not increase the dementia risk, in vivo and in vitro studies have shown that PPIs could interact with the pathophysiological pathway of AD. Indeed, lansoprazole increased amyloid β production (Aß40 and Aß42 oligomers) by enhancing ß‐secretase activity and modulating γ‐secretase (Batchelor et al, ). By inhibiting the vacuolar proton pump in microglial lysosomes, PPIs could basify lysosomes and thus hamper the degradation of fibrillar β‐amyloid (Haenisch et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations